2013
DOI: 10.1111/josh.12039
|View full text |Cite
|
Sign up to set email alerts
|

Are Environmental Influences on Physical Activity Distinct for Urban, Suburban, and Rural Schools? A Multilevel Study Among Secondary School Students in Ontario, Canada

Abstract: Students' time spent in PA varies by school location and some features of the school environment have a different impact on students' time spent in PA by school location. Developing a better understanding of the environment-level characteristics associated with students' time spent in PA by school location may help public health and planning experts to tailor school programs and policies to the needs of students in different locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
3
18
2
1
Order By: Relevance
“…However, we also found that none of the school-level built environment characteristics examined in the study were significantly associated with our physical activity outcomes, a finding inconsistent with the literature. [7][8][9][10][11][12] Contrary to what we expected, when facilities were more accessible to students the likelihood of the CSEP guideline being met did not increase. Had student-level data also been available pertaining to their perceived access to these facilities, which has previously been positively associated with physical activity levels of students, 7 we may have observed some interaction effect.…”
Section: School and Student Physical Activitycontrasting
confidence: 55%
See 2 more Smart Citations
“…However, we also found that none of the school-level built environment characteristics examined in the study were significantly associated with our physical activity outcomes, a finding inconsistent with the literature. [7][8][9][10][11][12] Contrary to what we expected, when facilities were more accessible to students the likelihood of the CSEP guideline being met did not increase. Had student-level data also been available pertaining to their perceived access to these facilities, which has previously been positively associated with physical activity levels of students, 7 we may have observed some interaction effect.…”
Section: School and Student Physical Activitycontrasting
confidence: 55%
“…Consistent with the Canada Food Guide fruit and vegetable consumption recommendations for teens, 25 males who reported less than eight servings per day and females who reported less than seven servings per day were classified as having inadequate fruit and vegetable consumption. The demographic measures included grade (9,10,11,12), sex (male, female), and ethnicity (collapsed into white only, other). Age was not included in the analysis because of the high correlation with grade.…”
Section: Student-level Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools located in urban settings are less likely to have a dedicated gymnasium or access to outdoor spaces (Dyson et al, 2009; Fernandes & Sturm, 2010; Hobin et al, 2013). Just as joint-use agreements can extend the use of school facilities to parents and community members (Jones & Wendel, 2015), agreements or permits with nearby community parks and playgrounds, universities, or recreation centers can support students’ use of facilities that are not available at school in order to connect students with community opportunities for physical activity to extend their learning in PE (Chase et al, 2011; Doolittle & Rukavina, 2014).…”
Section: Engage Community Partners To Address Structural Challengesmentioning
confidence: 99%
“…Seven years later, many of those considerations remain relevant, such as large class sizes (Dyson, Coviello, DiCesare, & Dyson, 2009; Schmidlein, Vickers, & Chepyator-Thomson, 2014) and limited access to equipment (Schmidlein et al, 2014), a dedicated gymnasium (Fernandes & Sturm, 2010), or outdoor space (Dyson et al, 2009; Hobin et al, 2013). These structural challenges matter.…”
mentioning
confidence: 99%